Price-directed search, product differentiation and competition - Martin Obradovits; Philipp Plaickner (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2022)
Especially in many online markets, consumers can readily observe prices, but may need to further inspect products to assess their suitability. We study the effects of product differentiation and search costs on competition and market outcomes in a tractable model of price-directed consumer search. We find that (i) firms' equilibrium pricing always induces efficient search behavior, (ii) for relatively large product differentiation, welfare distortions still occur because some consumers (may) forgo consumption, and (iii) lower search costs lead to stochastically higher prices, increasing firms' expected profits and decreasing their frequency of sales. Consumer surplus often falls when search costs decrease.
Keywords: D43; D83; L13; 330; Consumer Search; Price-Directed Search; Product Differentiation; Price Competition; Mixed-Strategy Pricing; Search Costs